EFL Students’ Perceptions of The Benefits of Project-Based Learning in Translation Class - Diah Astuti; Suhartini Syukri; Sitti Nurfaidah; Dewi Atikah (International Journal of Transdisciplinary Knowledge, 2021)
This study aims to describe students’ perceptions of the benefits of project-based learning in translation class. The project focuses on the students’ perceptions and the benefits of translation project. The research method uses a qualitative approach with descriptive data analysis technique. The participants of this study consist of 25 university students. The qualitative data were analyzed by questionnaire and students’ reflection adopted from Siregar (2018). The results of the research revealed that the students’ responded positively to the benefits of PBL in Translation Class. It further shows that the project-based learning model can train creative thinking, collaboration, English skills improvement, and challenging hence it is suitable to be applied in Translation class